Teratocracy and Contemporary Political Power - Villa, Fernando Gil (International Journal of Criminology and Sociology, 2026)
This article introduces the concept of teratocracy to analyze contemporary forms of political power marked by the erosion of symbolic limits and the normalization of excess. Epistemologically, it aligns with the tradition of the criminological imagination articulated by Jock Young, reconnecting criminology and sociology through C. Wright Mills’ critique of abstracted empiricism. From a criminological perspective, it also draws on recent developments in zemiology and social harm approaches, shifting the analytical focus from crime to the production, normalization, and denial of harm. From an interdisciplinary perspective, the analysis examines processes of symbolic collapse and their implications for authority, responsibility, legitimacy, and social harm. Teratocracy is conceptualized not as governance without law, but as a mode of power organized around unbounded enjoyment, which reshapes moral boundaries and weakens mechanisms of accountability.